EVOLUTION OF MATHEMATICS AT CRU LOS SANTOS: QUANTITATIVE STUDY OF FOUR DECADES OF ACADEMIC ACTIVITY - M., Alcibíades Medina; G., Nohelys E. Díaz; Cedeño, Eliecer; Galástica, Narciso (Seven Editora, 2026)
This study analyzes the academic evolution of the School of Mathematics at the Los Santos Regional University Center (CRU) over forty years of institutional history. Through a quantitative and descriptive approach, various indicators related to academic activity are examined, such as student enrollment, graduates, academic offerings, faculty output, and participation in academic projects. Data were obtained from a graduate survey, institutional records, academic reports, and administrative documents corresponding to the study period. The results identify trends in enrollment growth, the strengthening of mathematics education, and the school's contribution to the academic development of the regional center. Furthermore, the analysis highlights the fundamental role of mathematics in scientific and professional training within the region. This work provides an institutional overview that contributes to understanding the historical evolution of mathematics education at the Los Santos CRU and offers insights for future academic planning.